Is Poverty in the African DNA (Gene)? - Simplice A. Asongu; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2015)
A 2015 World Bank report on attainment of Millennium Development Goals concludes that the number of extremely poor has dropped substantially in all regions with the exception of Sub-Saharan Africa. We assess if poverty is in the African gene by revisiting the findings of Ashraf and Galor (2013, AER) and reformulating the 'Out of Africa Hypothesis' into a 'Genetic Diversity Hypothesis' for a 'Within Africa Analysis'. We motivate this reformulation with five shortcomings arising for the most part from the 2015 findings of the African Gerome Variation Project, notably: limitations in the concept of space, African dummy in genetic diversity, linearity in migratory patterns, migratory origins and underpinnings of genetic diversity in Africa. Ashraf and Galor have concluded that cross-country differences in development can be explained by genetic diversity in a Kuznets pattern. Our results from an exclusive African perspective confirm the underlying hypothesis in a contemporary context, but not in the historical analysis. From a historical context, the nexus is U-shaped for migratory distance, mobility index and predicted diversity while for the contemporary analysis; it is hump-shaped for ancestry-adjusted predicted diversity. Hence, poverty is not in the African gene from a within-Africa comparative standpoint. Policy implications are discussed.
Keywords: N10; N30; N50; O10; O50; Z10; 330; Africa; Genetic diversity; Comparative economic development